∵m≠n,∴
1 |
m |
1 |
n |
得
1 |
m2 |
5 |
m |
根據(jù)
1 |
m2 |
5 |
m |
1 |
n2 |
5 |
n |
∴
1 |
m |
1 |
n |
∴
1 |
m |
1 |
n |
解法二:由
1 |
n2 |
5 |
n |
根據(jù)2m2-5m-1=0與2n2-5n-1=0的特征,且m≠n,
∴m與n是方程2x2-5x-1=0的兩個不相等的實數(shù)根(6分)
∴m+n=
5 |
2 |
1 |
2 |
∴
1 |
m |
1 |
n |
m+n |
mn |
| ||
?
|
pq+1 |
q |
1 |
q |
1 |
q |
1 |
q |
1 |
q |
1 |
q |
pq+1 |
q |
1 |
n2 |
5 |
n |
1 |
m |
1 |
n |
1 |
m |
1 |
n |
1 |
m2 |
5 |
m |
1 |
m2 |
5 |
m |
1 |
n2 |
5 |
n |
1 |
m |
1 |
n |
1 |
m |
1 |
n |
1 |
n2 |
5 |
n |
5 |
2 |
1 |
2 |
1 |
m |
1 |
n |
m+n |
mn |
| ||
?
|